Peran Staffing dalam Pemberdayaan Sekolah di SMP Muslimin 5 Kota Bandung - Nurmalasari, Inten; Syah, Muhibbin (Universitas Islam Negeri Raden Intan Lampung, 2019)
AbstractThe facts in the field of work programs at school do not run smoothly because the duties and responsibilities are not given to the right people. So this will extinguish the potential of other teachers who have expertise in the field. This research aims to identify the Staffing process in Muslim 5 Junior High School in Bandung City, and analyze the school empowerment process so that educators and education staff are able to hone their skills in their fields more deeply. The results showed: 1) staffing management in Bandung 5 Junior High School in Bandung was based on school needs and the need for the learning process, things that were done were not too theoretical such as planning, selection and employment contracts; 2) School empowerment is based on the organizational structure that has been made the selection and appointment of teachers in certain job placements considered by taking into account various aspects, such as the length of service; educational qualifications and skills possessed; and 3) The impact of this organizational structure-based school empowerment is to reduce the vacancy of teaching hours because teachers who are unable to attend are present so that the teaching and learning process continues to be effective, efficient and conducive.Keywords: Staffing; Empowerment; School